Evaluation of the Surface Hardness and Roughness of a Resin-Modified Glass Ionomer Cement Containing Bacterial Cellulose Nanocrystals - Maryam Saadat; Marzieh Moradian; Babak Mirshekari (Hindawi Limited, 2021)
The purpose of this study was to evaluate the performance of a resin-modified glass ionomer cement (RMGIC) to which bacterial cellulose nanocrystals (BCNs) were added. BCNs were incorporated into the RMGIC powder in ratios of 0.3%, 0.5%, and 1% (w/w). One control and three experimental groups were enrolled in the study: unmodified RMGIC (control), 0.3% (w/w) BCN-modified RMGIC, 0.5% (w/w) BCN-modified RMGIC, and 1% (w/w) BCN-modified RMGIC. The surface hardness and surface roughness were the parameters assessed. The materials were characterized by scanning electron microscopy (SEM). The data were analyzed using the one-way ANOVA and Kruskal-Wallis tests for surface hardness and roughness, respectively. The addition of BCN resulted in the improvement of surface roughness in all the specimens compared with the control material. The RMGIC modified by 1% (w/w) BCN showed the lowest surface roughness (decreased by 52%) among all tested groups. However, BCN had a negative effect on the surface hardness of RMGIC. The group with 0.3% (w/w) BCN had the least decrease in microhardness (13%). According to the results, the RMGIC group modified by 1% (w/w) BCN had a smoother surface than the other groups. The surface microhardness of the RMGIC decreased after BCNs were added to it.